The experiences of high performance women coaches: A case study of two regional sport organisations - Shaw, S.; Allen, J. B. (Sport Management Review, 2009)
The purpose of this study was to examine the experiences of high performance female coaches and their managers. These experiences were examined through an analysis of the organisational values that related to the management of high performance women coaches. Specifically, organisational values were identified as powerful discourses that were key to framing coaches` and managers` organisational experiences, and also through which managers and coaches influence those experiences. The research utilised a case study approach of two Regional Sport Organisations in New Zealand. Commonalities and contradictions experienced by coaches and their managers were analysed. Additionally, analysis across the two organisations was undertaken. It was found that coaches and their managers do not just reflect their organisational values. Rather, they are at times active in constructing them. In order to consider and facilitate change in the management of high performance coaches, there is a need to consider this process of the creation of organisational values.